2014
DOI: 10.1111/jnc.12744
|View full text |Cite
|
Sign up to set email alerts
|

Peptidylarginine deiminases: novel drug targets for prevention of neuronal damage following hypoxic ischemic insult (HI) in neonates

Abstract: Neonatal hypoxic ischaemic (HI) injury frequently causes neural impairment in surviving infants. Our knowledge of the underlying molecular mechanisms is still limited. Protein deimination is a post-translational modification caused by Ca+2-regulated peptidylarginine deiminases (PADs), a group of five isozymes that display tissue-specific expression and different preference for target proteins. Protein deimination results in altered protein conformation and function of target proteins, and is associated with ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(110 citation statements)
references
References 40 publications
5
104
1
Order By: Relevance
“…Previous studies on in vivo models of CNS damage showed that PAD-upregulation and increased protein deimination lead to vast neuronal death which was preventable by pharmacological PAD inhibition, significantly reducing neuroinflammatory responses and histone H3 deimination, which has implications in gene regulation [23,[33][34][35]. In addition we have observed increased PAD expression during disease progression in tau mutation mouse models compared to age-matched controls [36].…”
Section: Introductionsupporting
confidence: 51%
See 4 more Smart Citations
“…Previous studies on in vivo models of CNS damage showed that PAD-upregulation and increased protein deimination lead to vast neuronal death which was preventable by pharmacological PAD inhibition, significantly reducing neuroinflammatory responses and histone H3 deimination, which has implications in gene regulation [23,[33][34][35]. In addition we have observed increased PAD expression during disease progression in tau mutation mouse models compared to age-matched controls [36].…”
Section: Introductionsupporting
confidence: 51%
“…Administration of one dose of Cl-Am (80 mg/kg) straight after injury and up to two hours post-injury, in a chick-model of spinal cord damage, significantly reduced neuronal cell death, tissue loss and histone H3 deimination, compared to non-treated control injuries [32]. In two different mouse models of neonatal hypoxic ischaemic encephalopathy (HIE), firstly where permanent left carotid occlusion was followed with severe hypoxia (8% oxygen for 60 min), or secondly with 30 min hypoxia in combination with infection (as mimicked by LPS stimulation), one dose of Cl-Am (30 mg/kg) straight after hypoxia, or 10 min after LPS stimulation and again straight after hypoxia, significant reduction was observed in microglial activation, histone H3 deimination and cell death in all affected brain regions [33]. Interestingly, EV release has previously been associated with cerebral hypoxia induced by acute ischaemic stroke [93,94] while increased protein deimination has also been detected in the pathology of traumatic brain injury [95].…”
Section: Pads In Central Nervous System (Cns) Damage and Neuroprotectmentioning
confidence: 99%
See 3 more Smart Citations